P. S. Post Scriptum. Dos corpus diacrónicos de escritura cotidiana - Vaamonde, Gael (2018)
In this paper, we present an overall description of P. S. Post Scriptum. Within this research project, systematic research will be developed, along with the publishing and historical-linguistic study of private letters written in Portugal and Spain along the Modern Ages. The letters included in P. S. Post Scriptum are unpublished manuscripts, written by authors from different social backgrounds. In addition, these textual resources often present an (almost) oral rhetoric, treating everyday issues of past centuries. They are, therefore, of great interest for research in Diachronic Linguistics. We aim to publish and study 7,000 of those letters. For this purpose, we are preparing a scholarly digital edition of the manuscripts and, simultaneously, converting the content of the letters into two annotated corpora of a million words each, one containing the Portuguese letters, the other the Spanish.